J. Max Bond Jr. and the Appropriation of Modernism in a Library Design in Ghana. Issue 3 (2nd September 2018) - Balaara, Allan Stephen; Haarhoff, Errol; Melis, Alessandro
ABSTRACT: The paper draws on the architect, J. Max Bond Jr.'s architectural influences in the context of his design response to the Bolgatanga Regional Library, with the aim of advancing the idea of hybrid modernism in postcolonial Ghanaian architecture. Bond considered the Library his first independent work and the most profound. However, as an architect-academic working alongside several celebrated modernist practitioners, Bond's Library appears to have had strong influences. Bond's expression of modernism in the Library reflects the mediation of three cultures: the northern vernacular building culture; the principles of Western modernism; and his hybrid background as an African-American architect. His response, while much like other socio-climatic responses in late tropical practices in Ghana, also demonstrates how the architecture of the marginalised manifested in the use of concrete also constitutes a reflection of the postcolonial mediation of space.